Low Body Mass Index for Early Screening of Adolescent Idiopathic Scoliosis: A Comparison Based on Standardized Body Mass Index Classifications - Suhee Kim; Ju-Yeon Uhm; Duck-Hee Chae; Yunhee Park (Elsevier, 2020)
Purpose: Scoliosis is a common musculoskeletal problem in adolescents. This study aimed to identify the prevalence of adolescent idiopathic scoliosis (AIS) and its associated factors among Korean adolescents. The prevalence of thin individuals among students with AIS was compared based on body mass index (BMI) classifications. Methods: This study was a secondary data analysis and used the 2016 Korean National Health Examination for School Students data. Data from 16,412 students were analyzed using descriptive statistics, Chi-square tests, and logistic regression analysis. Results: The prevalence of AIS was higher in women (3.8%) than in men (1.6%), and a higher school year was a risk factor for AIS in both sexes. In woman adolescents, scoliosis was associated with thinness; however, the risk of AIS was inversely associated with overweight/obesity in both sexes. The prevalence of thin woman students with scoliosis differed based on the criteria used: 3.3% by the World Health Organization criteria and 14.3% by the International Obesity Task Force criteria. Conclusion: The prevalence of thin students with scoliosis could increase by up to four times depending on the BMI criteria. For early screening of thin people at risk of AIS among female students, the criterion of International Obesity Task Force should be used as it is more permissive of thinness. This is also because of the underestimation of AIS prevalence when using the BMI Z score of the World Health Organization cutoff. Keywords: adolescent, body mass index, scoliosis, thinness